First Detection of Human Coronavirus HKU1 in Greece, in an Immunocompromised Patient With Severe Lower Respiratory Tract Infection - Georgakopoulou, Vasiliki Epameinondas; Petsinis, Georgios; Mantzouranis, Konstantinos; Damaskos, Christos; Melemeni, Despoina; Gkoufa, Aikaterini; Chlapoutakis, Serafeim; Garmpis, Nikolaos; Sklapani, Pagona; Trakas, Nikolaos; Tsiafaki, Xanthi (Acta medica Lituanica, 2021)
Human coronavirus HKU1 (HCoV-HKU1) is a RNA virus which gets in the human cells by binding to the receptor of N-acetyl-9-O-acetylneuraminic acid. Human Coronaviruses (HCoVs), including HCoV-HKU1, are globally found. HCoV-HKU1 is responsible for upper and lower respiratory tract infections, usually with mild symptoms. In severe cases, HCoV-HKU1 can cause life-threatening respiratory illness especially in vulnerable hosts such as elderly, children and immunocompromised patients. In Greece, Respiratory Syncytial Virus (RSV) and influenza are the most common viruses causing respiratory tract infections. Traditionally, HCoVs are responsible for less than 3% of respiratory infections in Greek population. HCoVs 229E and OC43 have been shown to circulate in Greece. We report the first case of lung infection in an immunocompromised woman due to HCoV-HKU1, that has never been before detected in Greece. HCoV-HKU1 is related to severe disease even in healthy individuals and must be considered in the differential diagnosis of severe respiratory infections.